THE EFFECTS OF SILVER NANOPARTICLES ON GROWTH OF Chrysanthemum morifolium Ramat. cv. "JIMBA" IN DIFFERENT CULTURAL SYSTEMS - Nghia, Luong Thien; Tung, Hoang Thanh; Huy, Nguyen Phuc; Luan, Vu Quoc; Nhut, Duong Tan (Vietnam Journal of Science and Technology, 2017)
Silver nanoparticles (SNPs) are one of metallic nanoparticles widely applied in many fields. Research of SNPs application in plant tissue culture has been gaining attention in recent years. Moreover, novel plant tissue culture systems have been researched and developed for improving SNPs uptake capability in medium. In this study, we investigated effects of SNPs on Chrysanthemum morifolium ramat. cv. "JIMBA" growth and its ability in 3 culture systems: in vitro solid medium system, in vitro liquid medium system and microponic (combined of micropropagation and hydroponic). The 3 cm Chrysanthemum shoots and silver nanoparticles of diameter smaller than 20 nm were used in the experiments. After 4 weeks, the results showed that the SNPs concentration was suitable for growth of Chrysanthemum in vitro solid medium system, in vitro liquid medium system and microponic was 1.5, 1.5 and 5 ppm, respectively. Microponic system not only improved plant growth but also reduced the succulent phenomenon. SNP uptake was likely dependent on concentrations and culture systems. At low concentrations (1, 5, and 10 ppm), SNPs were completely absorbed after 4 weeks of culture in all systems, but not at high concentrations (20 ppm). The amount of absorbed silver nanoparticles was directly proportional to the culture period and inversely proportional to the concentration of SNPs supplemented to the medium. In all of our investigated systems, the hydroponic system showed the highest capability of SNPs absorption.